Strengthening Application-Based Digital Health Literacy in The Prevention and Management of Stunting among Mothers with Children Under Five Years of Age - Dyah Noviawati Setya Arum; Masrif Masrif; Atik Ismiyati; Sumarah Sumarah; Nuning Marina Pengge; Linda Nur Wahyuni (Jurnal Bidan Cerdas, 2025)
Background: The rapid advancement of information technology has significantly transformed access to health information. However, the emergence of online media as a major information channel has also brought negative consequences, such as the widespread dissemination of misinformation, particularly when not accompanied by adequate digital literacy skills. This study aimed to analyze the effect of strengthening digital health literacy among mothers with children under five years of age in preventing and managing stunting. Methods: A quasi-experimental study with a two-group pre-posttest design was conducted involving 112 mothers of children under five with stunting, divided into control (n=56) and intervention (n=56) groups. Samples were selected using simple random sampling. A web-based application, Cegating, was developed and tested for usability using the System Usability Scale (SUS). Respondents’ knowledge was measured using a structured questionnaire. Data were analyzed using univariate and bivariate approaches with SPSS software. Results: The usability test of Cegating yielded a SUS score of 89.8%. In the intervention group, the mean knowledge score increased from 62.52 (pre-test) to 64.79 (post-test) (p=0.001). In the control group, the mean score increased from 60.68 to 63.30 (p=0.029). Conclusion: Strengthening digital health literacy improved mothers’ knowledge in preventing and managing stunting. The Cegating application is feasible and effective as an educational tool to enhance health education strategies for mothers with children under five to prevent and address stunting.